Loose Women on Men - Hodder and Stoughton (London Hodder and Stoughton, 2010)
The bestselling brand returns as the girls let loose on their favourite subject - MEN!
Include Illustration
Keywords: Man-woman relationships -- Men -- Men--Psychology